Cancer's sweet spot: techniques to harness saccharides in tumor biology - Jade Parker (BioTechniques)
All of the cells in our bodies are enveloped in sugar, this sweet coating plays a particularly interesting and crucial role in tumor biology. Here, we review the techniques being used to detect and exploit cancer's sweet spot. including click chemistry, glycoproteomic profiling and bioorthogonal chemistry.